Comparison of Laboratory Profiles of Cerebrospinal Fluid among Bacterial and Viral Meningitis Patients - Habiba, Umme; Hossain, Md Akram; Mahmud, Md Chand; Bhuiyan, Md Sirajul Islam; Rafique, Md Ali Abdullah; Sultana, Safia (Journal of National Institute of Neurosciences Bangladesh, 2021)
Background: Laboratory profiles are important markers for the detection of meningitis. Objective: The purpose of the present study was to compare of laboratory profiles of cerebrospinal fluid among bacterial and viral meningitis patients. Methodology: This cross sectional study was carried out in the Department of Microbiology at Mymensingh Medical College, Mymensingh, Bangladesh from July 2010 to January 2012 for around 2 years. Clinically suspected patients with meningitis from paediatrics wards of MMCH, Mymensingh, Bangladesh were included in this study. On the basis of cytological tests and biochemical tests of CSF the study subjects were categorized into three groups, which were identified as bacterial meningitis, viral meningitis and normal CSF. After collection of CSF, physical examination, routine bed side culture and appropriate biochemical tests were performed. Tests for protein and glucose of CSF specimens were performed. Result: A total 115 clinically and laboratory confirmed meningitis patients were enrolled in this study. The most of the cases of study population were in the age group 1 month to 5 years 97(84.3%) cases. Regarding the physical findings of CSF, purulent was found 21(60.0%) cases in bacterial meningitis and 14 (40.0%) cases were slightly turbid. The mean with SD of total count of WBC was higher in bacterial meningitis (1623.1±1708.06/mm3) than viral meningitis (56.0±73.83/mm3) (p=<0.001). Again the mean with SD of glucose was lowest in bacterial meningitis which was 21.0±9.77 mg/dL followed by viral meningitis which was 63.6±20.22 mg/dL. (p<0.001). Considering protein of CSF the mean with SD was highest in bacterial meningitis which was 242.8±188.09 mg/dL followed by viral meningitis which was 69.6±84.67mg/dL (p<0.001). Conclusion: In conclusion the WBC count, CSF glucose and protein are significantly differ in bacterial and viral meningitis. Journal of National Institute of Neurosciences Bangladesh, January 2021, Vol. 7, No. 1, pp. 69-74